Isolation and characterization of lignin from okra (Abelmoschus esculentus) fibre and stick - Jahan, M Sarwar; Alam, D; Rahman, M Mostafzur; Quaiyyum, MA (Bangladesh Journal of Scientific and Industrial Research, 2015)
The okra (Abelmoschus esculentus) plant consists of bast fiber and core (stick). The bast fibre of okra plant was characterized with high ?-cellulose (56.7%) and low lignin (12.6%) and stick withlow ?-cellulose (34.3%) and high lignin (25.2%) content. Lignin was isolated from the fiber and stick by acidolytic dioxane method and characterized for elemental analysis, methoxyl analysis and FTIR and 1H-NMR spectroscopy. The C9 formulas for okra stick and fibre lignin were C9H9.61O4.63(OCH3)1.24 and C9H8.61O4.66(OCH3)1.49, respectively. Both of the lignins were of the guaiacyl-syringyl type. The bands of FT-IR spectrum at 1327 cm-1, 1122 cm-1 and 837 cm-1 associated with syringyl unit was higher in okra fibre lignin than in the okra stick lignin. The structural analysis revealed that the average numbers of proton of ?-O-4 (H? & H?) per C9 unit in okra stick and fibre lignin were 1.53 and 1.20, respectively. The ?-O-4 units in these lignins had predominately erythro stereochemistry type. Bangladesh J. Sci. Ind. Res. 50(4), 257-262, 2015